Evaluation of palatal prosthesis for the treatment of velopharyngeal dysfunction Avaliação de pacientes portadores de disfunção velofaríngea tratados com prótese de palato - João Henrique Nogueira Pinto; Maria Inês Pegoraro-Krook (University of São Paulo, 2003)
Some patients presenting velopharyngeal dysfunction need treatment with a palatal prosthesis, and few researches attempt to evaluate the judgement of its efficacy. For that reason, a questionnaire was submitted to 48 patients with a palatal prosthesis, with ages from 8 to 74 (mean 31.47), from which 42 had a congenital cleft, 2 exhibited an acquired cleft and 4 presented total or partial palsy of the soft palate. Results reveled that 81.2% of these patients were able to eat while using their prostheses; 85.4% stated their speech had improved with the prostheses; 75% considered the prosthesis stable during nourishment, and 91.7% during speech; 79.2% felt comfortable using the prosthesis; and 85.4% related a general improvement in life quality with the prosthetic treatment of velopharyngeal dysfunction. It was concluded that the prosthetic treatment of velopharyngeal dysfunction demonstrated efficacy in improving speech, despite of the heterogeneous sample. Besides, it offered the other basic requirements of a prosthesis whenever it was needed. O trabalho avaliou a efetividade do tratamento da disfunção velofaríngea com prótese de palato. A amostra consistiu em 48 pacientes, com idades variando entre 8 e 74 anos (X = 31,47±16,03), sendo 42 com insuficiência velofaríngea devido à fissura palatina congênita operada ou não, 2 com insuficiência velofaríngea devido à ressecção total ou parcial do palato (casos que tiveram câncer) e 4 com incompetência velofaríngea devido à paralisia total ou parcial do palato mole. Os resultados do questionário mostraram que: (1) a maioria dos pacientes preferiu se alimentar usando a prótese (81,2%); (2) a maioria relatou melhora da fala com a prótese (85,4%); (3) a prótese ficou estável para a maioria dos pacientes, tanto na alimentação (75%), quanto na fala (91,7%); (4) a maior parte dos pacientes (79,2%) sentiram-se confortável em usar a prótese; (5) a estética com a prótese foi satisfatória para a maioria dos pacientes (97,9%); (6) a qualidade de vida da maioria dos pacientes (85,4%), melhorou com o uso da prótese.